Innovation in Latin America: An Eternal Recurrence? - Montiel, Oscar (Emerald Publishing, 2022)
The chapter analyzed the conditions and challenges of the innovation in Latin America, and the historical trend in its study in the framework of this handbook. The transformative and inclusive approach of the innovation was evidenced as the most significant ascendent trend in the region. Furthermore, this was identified as a breaking point of the linear individualism of the entrepreneurship and the innovation in Latin America due to this type of innovation that requires high levels of collaboration and strong institutional leaderships. It was highlighted that the major challenge of recovery in the region should be accompanied by a deep transformation in the quality of education because the systematic generation of innovation implies capabilities rather than wills. The chapter closes with a critical reflexion of the phenomenon, the new lines of research in the region, and its implications.